DEVELOPMENT MATHEMATIC MODULE OF SET MATERIAL FOR STUDENTS IN GRADE VII SMP/MTs BASED ON CURRICULUM 2013 - Habibah Putri Pertiwi; Sumargiyani Sumargiyani (Universitas Ahmad Dahlan, 2018)
This research aims to develop a mathematical module on the set material for students of class VII Junior High School (SMP/MTs) based on the 2013 curriculum and know the feasibility of modules developed based on material experts, media experts, and student's responses. The type of this research is the development research, which refers to the model of ADDIE, namely Analysis, Design, Development, Implementation, and Evaluation. The instruments used in this study are an assessment sheet for material experts, assessment sheets for media experts, and a student response questionnaire to the module. The subjects of this study are material experts, media experts, and students of SMPN 15 Yogyakarta and MTs Muhammadiyah Karangkajen Yogyakarta. The results of this research and development show that the module The mathematics developed included in the category is a very well based questionnaire assessment by a material expert with a score of 137.667; Questionnaire assessment by expert media with a score 128,667; and average student response results in this study is 124,427. The assessment results show that the mathematics module, the set material for grade VII students of SMP / MTs based on the 2013 curriculum, is worthy of use in the learning process.